We had the Watches. They had the Time - Burke, Carol. author. aut Link
XIX, 223 p. 15 illus., 13 illus. in color.
Keywords: This book focuses on the war in Afghanistan. In 2010 and 2011, the author took a leave from her faculty position at the University of California, Irvine to train and then deploy as a cultural advisor with two U.S. Army combat units in Afghanistan. Her account begins with the U.S. Army’s four-month training program for cultural advisors, follows her deployment, much of it on missions to remote and volatile areas far from brigade headquarters, and concludes with her uneasy return home. She examines the everyday lives of Americans sent to conduct a war of counterinsurgency, including their sexual exploits on base, their superstitions, even the heroic accounts that military contractors recount in their personal stories of past wars, stories that are sometimes a little too good to be true. In turn, she explores the views of ordinary Afghans to this American occupation. Carol Burke is Professor Emerita in English at UC Irvine, and Visiting Scholar in University of North Carolina’s Program in Peace, War and Defense. She combines her ethnographic skills as a folklorist with her interest in literary journalism. Publications include Camp All-American, Hanoi Jane, and the High-and-Tight, a study of military culture; Women’s Visions, a book that explores accounts of the supernatural and the uncanny exchanged by women in prison; The Creative Process (coauthored with Molly Tinsley), a creative writing text; Plain Talk and Back in Those Days, collections of family folklore--the latter coauthored with Martin Light; and Close Quarters, a collection of poems. Articles have appeared in magazines like The Nation and The New Republic as well as scholarly journals and collections. Before joining the faculty at UCI in 2004, Professor Burke taught courses in literary journalism at Vanderbilt and Johns Hopkins Universities.